2014
DOI: 10.1126/science.1256224
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of the transition state for pressure-induced BO 3 → BO 4 conversion in glass

Abstract: A fundamental mechanistic understanding of the pressure- and/or temperature-induced facile transformation of the coordination environment of boron is important for changing the physical properties of glass. We have used in situ high-pressure (up to 2 gigapascals) boron-11 solid-state nuclear magnetic resonance spectroscopy in combination with ab initio calculations to investigate the nature of the transition state for the pressure-induced BO3→ BO4 conversion in a borosilicate glass at ambient temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…For example, Stebbins et al found a conversion of BO 3 trigonal to BO 4 tetrahedral with increasing temperature. 11) Recently, Edwards et al 12) discovered the dynamic process of the BO 3 →BO 4 conversion with increasing pressure using a high pressure 11 B solid state Nuclear Magnetic Resonance (NMR) spectroscopy. There appears a deformation of the BO 3 planar triangle into trigonal pyramid, which serves as a precursor for the formation of BO 4 tetrahedral.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stebbins et al found a conversion of BO 3 trigonal to BO 4 tetrahedral with increasing temperature. 11) Recently, Edwards et al 12) discovered the dynamic process of the BO 3 →BO 4 conversion with increasing pressure using a high pressure 11 B solid state Nuclear Magnetic Resonance (NMR) spectroscopy. There appears a deformation of the BO 3 planar triangle into trigonal pyramid, which serves as a precursor for the formation of BO 4 tetrahedral.…”
Section: Introductionmentioning
confidence: 99%
“…In the report of Edwards et al [11] it was established that the out-of-plane displacement of the boron atom is consistent with the in situ high-pressure NMR spectra. This mode of deformation for the 11 Bδ iso value is given in Figure 2.…”
Section: T Hoff Modellingmentioning
confidence: 58%
“…This mode of deformation for the 11 Bδ iso value is given in Figure 2. Out-of-plane displacement of boron in B(OH) 3 following the characteristics of the Van't Hoff (vtH) modelling under subsequent formation of a tetrahedral configuration.…”
Section: T Hoff Modellingmentioning
confidence: 99%
See 2 more Smart Citations